Peningkatan Keterampilan Bahasa Inggris SMPN 19 Mataram Melalui Model Triple P - Lela Rahmawati; Sutarman Sutarman (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
SMPN 19 Mataram which is in the area of ​​Jalan DR. Soedjono Lingkar Selatan No.14, Dasan Cermen, Sandubaya district, Mataram City, West Nusa Tenggara. Because the location of the school is included in the suburbs and the English language skills at the school are still low. Based on the conditions above, the Teaching team is interested in conducting education service by providing an English language course using Triple P model for the students in SMPN 19 Mataram. This course used the media Triple P (Present, Practice, Production) method with the aim of making the course activities more interesting and easier for the course participants. This English coursing activity has a positive impact on the students in SMPN 19 Mataram. These positive impacts are seen through the result of the coursing process. Within a few months of following the coursing process by using Triple P media, the learning outcomes of the training participants increased. Before participating in the coursing, the coursing participants considered English was a difficult language to learn, but after participating in the coursing by using Triple P media the students began to experience the convenience and the students thought that learning English using Triple P media was fun.